The Effect of Technology and Digitalization on the Quality Management System among Omani and Gas Drilling Company. - Ali Malik, Al Harthy; Sagaran, Gopal; Said M., Al-Saqri; Hock, Oo Yu (2018)
This paper presents the mediate effect of technology and digitalization on the relationship between preventative maintenance (equipment related) and overall performance (Quality Management System) among an Omani oil and gas drilling company. Technology and digitalization is considered to be one of the key factors to improve and sustain the overall performance. The paper presents a comprehensive assessment in the overall performance of a drilling rig before and after introducing mechanization operated by one company. A case study will be considered to compare the existing conventional drilling rig performance before and after mechanization, operating at the same concession area, in terms of cost, well delivery, non-productive timing and HSE using a graph form. The overall trend between the two different types of rig design is determined.